Measuring Perceptions of Consumer Destination Image, Destination Familiarity, E-WOM, Destination Trust with Destination Choices - Priya Bai; Muhammad Muzamil Sattar; Vijay Kumar (Centre For Tourism Planning and Development, 2022)
Current theory in tourism marketing lacks understanding of how businesses signal trust to consumers to make destination-based choices. The present research investigates the role of E-WOM, destination image, familiarity, and trust (as mediator) in destination choice from signaling theory perspective. The theory suggests that there is asymmetric information between the receiver and sender which can be resolved by communicating various positive signals. This study aims to test interrelationships among these variables on destination choice. A random sample of 382 consumers having experience of travelling to the northern areas of Pakistan participated in this study. Data was analyzed through SmartPLS. The research findings highlight relationship among factors which plays a significant role for destination choice. The findings further indicate that destination trust act as a positive signal for consumers which in turn influences their destination choice (consumer perceive). Furthermore, for tourists visiting northern areas of Pakistan positive E-WOM, destination image and familiarity create signals to influence destination trust. Implications of the findings for theory and practices are considered along with future research directions.